Improvement of the mechanical properties and osteogenic activity of 3D-printed polylactic acid porous scaffolds by nano-hydroxyapatite and nano-magnesium oxide - Dian Xu; Zexian Xu; Lidi Cheng; Xiaohan Gao; Jian Sun; Liqiang Chen (Heliyon, 2022)
Porous bone scaffolds based on high-precision 3D printing technology gave recently been developed for use in bone defect repair. However, conventional scaffold materials have poor mechanical properties and low osteogenic activity, limiting their clinical use. In this study, a porous composite tissue-engineered bone scaffold was prepared using polylactic acid, nano-hydroxyapatite, and nano-magnesium oxide as raw materials for high-precision 3D printing. The composite scaffold takes full advantage of the personalized manufacturing features of 3D printers and can be used to repair complex bone defects in clinical settings. The composite scaffold combines the advantages of nano-hydroxyapatite, which improves the formability of scaffold printing, and of nano-magnesium oxide, which regulates pH during degradation and provide a good environment for cell growth. Additionally, nano-magnesium oxide and nano-hydroxyapatite have a bidirectional effect on promoting the compressive strength and osteogenic activity of the scaffolds. The prepared composite porous scaffolds based on 3D printing technology show promise for bone defect repair.